Extinction of Aversive Classically Conditioned Human Sexual Response. (17th December 2014) - Brom, Mirte; Laan, Ellen; Everaerd, Walter; Spinhoven, Philip; Both, Stephanie
Abstract Introduction Research has shown that acquired subjective likes and dislikes are quite resistant to extinction. Moreover, studies on female sexual response demonstrated that diminished genital arousal and positive affect toward erotic stimuli due to aversive classical conditioning did not extinguish during an extinction phase. Possible resistance to extinction of aversive conditioned sexual responses may have important clinical implications. However, resistance to extinction of aversive conditioned human sexual response has not been studied using extensive extinction trials. Aim This article aims to study resistance to extinction of aversive conditioned sexual responses in sexually functional men and women. Methods A differential conditioning experiment was conducted, with two erotic pictures as conditioned stimulus (CSs) and a painful stimulus as unconditioned stimuli (USs). Only one CS (the CS+) was followed by the US during the acquisition phase. Conditioned responses were assessed during the extinction phase. Main Outcome Measure Penile circumference and vaginal pulse amplitude were assessed, and ratings of affective value and subjective sexual arousal were obtained. Also, a stimulus response compatibility task was included to assess automatic approach and avoidance tendencies. Results Men and women rated the CS+ more negative as compared with the CS−. During the first trials of the extinction phase, vaginal pulse amplitude was lower in response to the CS+ than in response to the CS−, and on the first extinction trial women rated the CS+ as less sexually arousing. Intriguingly, men did not demonstrate attenuated genital and subjective sexual response. Conclusions Aversive conditioning, by means of painful stimuli, only affects sexual responses in women, whereas it does not in men. Although conditioned sexual likes and dislikes are relatively persistent, conditioned affect eventually does extinguish. Brom M, Laan E, Everaerd W, Spinhoven P, and Both S. Extinction of aversive classically conditioned human sexual response. J Sex Med 2015;12:916–935.